2023
DOI: 10.1007/s00705-022-05674-6
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive molecular survey of viral pathogens associated with canine gastroenteritis

Abstract: Viral pathogens are the primary cause of canine gastroenteritis. However, few structured comprehensive studies on the viral etiology of canine gastroenteritis have been conducted. In this study, 475 rectal swabs collected over three years (2018-2021) from clinical canine gastroenteritis cases were screened for the presence of six major enteric viruses – canine parvovirus 2 (CPV-2), canine distemper virus (CDV), canine adenovirus 2 (CAdV-2), canine coronavirus (CCoV), canine astrovirus (CaAstV), and canine rota… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
5
1
Order By: Relevance
“…Canine AstV has been reported to be associated with acute gastroenteritis or without clinical symptoms across the world. The only recently published study from the Hyderabad region of India reported a 7.2% prevalence of CAstV, and the strain with full genome sequence grouped with Chinese and Brazilian strains (Dema et al, 2023). In contrast, all the present study strains are grouped with a different cluster of Hungarian, Italian and Chinese strains.…”
Section: Discussioncontrasting
confidence: 58%
“…Canine AstV has been reported to be associated with acute gastroenteritis or without clinical symptoms across the world. The only recently published study from the Hyderabad region of India reported a 7.2% prevalence of CAstV, and the strain with full genome sequence grouped with Chinese and Brazilian strains (Dema et al, 2023). In contrast, all the present study strains are grouped with a different cluster of Hungarian, Italian and Chinese strains.…”
Section: Discussioncontrasting
confidence: 58%
“…Since the exact role of CaAstV remains unknown, further observational studies or animal experiments are needed to better understand the pathogenic role of CaAstV. There are studies attempting in vitro isolation of CaAstV; the results have been either successful isolation ( 4 , 55 ) or unsuccessful isolation ( 3 , 39 ). Therefore, the cultivation of CaAstV remains a major challenge at present.…”
Section: Discussionmentioning
confidence: 99%
“…Canine AstV has been reported to be associated with acute gastroenteritis or without clinical symptoms across the world. The only recently published study from the Hyderabad region of India reported a 7.2% prevalence of CAstV, and the strain with full genome sequence grouped with Chinese and Brazilian strains [ 26 ]. In contrast, all the present study strains are grouped with a different cluster of Hungarian, Italian and Chinese strains.…”
Section: Discussionmentioning
confidence: 99%